Barriers faces telemedicine implementation in the developing countries: toward building Iraqi telemedicine framework - Mohd Khanapi, Abd Ghani; Mustafa Musa, Jaber (2006-2014 Asian Research Publishing Network (ARPN), 2015)
The Iraqi healthcare services are tussling get possession of lost momentum. Many professional physicians and nurses left Iraq because the current situation there. In spite of the plans of calling back the skilled health workforce but they still afraid of disadvantage of their return. Hence, technology plays a central role to take advantage of their profession through the use of telemedicine. Thus it is the need to study the factors that effects the implementation of telemedicine that covers network services, policy makers and patient understanding. These papers shows the issue that faces the implementation of telemedicine and analyze the literature of previous telemedicine in Middle East countries to find out the essential factors toward building Iraqi telemedicine framework